Radical Interpretations of Jihad: A Double Movement Analysis of Q.S. al-Baqarah (2:191) - Hadi, Lalu Nuzul Ilham; Susilowati, Nuri; Huda, Ade Naelul (Ar-Rasikhin : Jurnal Ilmu Al-Qur'an dan Tafsir, 2026)
This article examines radical interpretations of Q.S. Al-Baqarah [2]:191 employed as theological justification for acts of terrorism, particularly the Bali Bombings. The study aims to analyze the hermeneutical errors underlying such interpretations and to offer a scholarly refutation through Fazlur Rahman’s Double Movement hermeneutical approach. Using a qualitative library research design, the study analyzes classical and contemporary Qur’anic commentaries, biographical accounts of the perpetrators, and relevant academic literature on jihad and radicalism. The findings reveal that radical interpretations arise from a rigid, ahistorical, and atomistic reading of the Qur’anic text that ignores its socio-historical context and ethical objectives. This study concludes that the Double Movement approach provides a contextual, defensive, and morally coherent understanding of jihad, aligning with the principles of maqāṣid al-sharī‘ah, and thus serves as an effective scholarly framework for countering ideological radicalization.